Association of HMIP1 C-893A polymorphism and disease severity in patients with sickle cell anemia - Pereira-Martins, Diego A. (2020)
Introduction: Sickle cell anemia (SCA) is a Mendelian disorder with a heterogeneous clinical course. The reasons for this phenotypic diversity are not entirely established, but it is known that high fetal hemoglobin levels lead to a milder course of the disease. Additionally, genetic variants in the intergenic region HBS1L-MYB promote high levels of fetal hemoglobin into adulthood. Objective: In the present study, we investigated the HMIP1 C-839A (rs9376092) polymorphism, located at the HBS1L-MYB intergenic region block 1, in SCA patients. Method: We analyzed 299 SCA patients followed in two reference centers in Brazil. The HMIP1 C-839A (rs9376092) genotypes were determined by allele specific polymerase chain reactions. Clinical and laboratory data were obtained from patient interviews and medical records. Results: The median fetal hemoglobin levels were higher in patients with the HMIP1 C-839A (rs9376092) AA genotype (CC = 6.4%, CA = 5.6% and AA = 8.6%), but this difference did not reach significance (p = 0.194). No association between HMIP1 C-839A (rs9376092) genotypes and other clinical and laboratorial features was detected (p > 0.05). Conclusion: In summary, our data could not support the previously related association between the HMIP1 C-893A (rs9376092) polymorphism and differential fetal hemoglobin levels.